Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the system of equations using the substitution method, follow these steps:
Given system of equations:
[tex]\[ \begin{array}{l} 2 x - y = 10 \quad \text{(Equation 1)} \\ 2 x - 2 y = 4 \quad \text{(Equation 2)} \end{array} \][/tex]
1. Solve for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] from Equation 1:
[tex]\[ 2 x - y = 10 \][/tex]
Rearrange to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 2 x - 10 \][/tex]
2. Substitute the expression for [tex]\( y \)[/tex] into Equation 2:
Substitute [tex]\( y = 2 x - 10 \)[/tex] into [tex]\( 2 x - 2 y = 4 \)[/tex]:
[tex]\[ 2 x - 2(2 x - 10) = 4 \][/tex]
3. Simplify and solve for [tex]\( x \)[/tex]:
[tex]\[ 2 x - 2(2 x) + 20 = 4 \\ 2 x - 4 x + 20 = 4 \\ -2 x + 20 = 4 \][/tex]
Subtract 20 from both sides:
[tex]\[ -2 x = 4 - 20 \\ -2 x = -16 \][/tex]
Divide both sides by -2:
[tex]\[ x = 8 \][/tex]
4. Substitute [tex]\( x = 8 \)[/tex] back into the expression for [tex]\( y \)[/tex]:
Using the expression [tex]\( y = 2 x - 10 \)[/tex]:
[tex]\[ y = 2(8) - 10 \\ y = 16 - 10 \\ y = 6 \][/tex]
5. Conclusion:
The solution to the system of equations is the ordered pair [tex]\((8, 6)\)[/tex].
Therefore, the correct answer is:
[tex]\[ \boxed{(8, 6)} \][/tex]
Given system of equations:
[tex]\[ \begin{array}{l} 2 x - y = 10 \quad \text{(Equation 1)} \\ 2 x - 2 y = 4 \quad \text{(Equation 2)} \end{array} \][/tex]
1. Solve for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] from Equation 1:
[tex]\[ 2 x - y = 10 \][/tex]
Rearrange to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 2 x - 10 \][/tex]
2. Substitute the expression for [tex]\( y \)[/tex] into Equation 2:
Substitute [tex]\( y = 2 x - 10 \)[/tex] into [tex]\( 2 x - 2 y = 4 \)[/tex]:
[tex]\[ 2 x - 2(2 x - 10) = 4 \][/tex]
3. Simplify and solve for [tex]\( x \)[/tex]:
[tex]\[ 2 x - 2(2 x) + 20 = 4 \\ 2 x - 4 x + 20 = 4 \\ -2 x + 20 = 4 \][/tex]
Subtract 20 from both sides:
[tex]\[ -2 x = 4 - 20 \\ -2 x = -16 \][/tex]
Divide both sides by -2:
[tex]\[ x = 8 \][/tex]
4. Substitute [tex]\( x = 8 \)[/tex] back into the expression for [tex]\( y \)[/tex]:
Using the expression [tex]\( y = 2 x - 10 \)[/tex]:
[tex]\[ y = 2(8) - 10 \\ y = 16 - 10 \\ y = 6 \][/tex]
5. Conclusion:
The solution to the system of equations is the ordered pair [tex]\((8, 6)\)[/tex].
Therefore, the correct answer is:
[tex]\[ \boxed{(8, 6)} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.